Rare copy number variation analysis identifies disease-related variants in atrioventricular septal defect patients - Hu, Huan; Geng, Zilong; Zhang, Shasha; Xu, Yuejuan; Wang, Qingjie; Chen, Sun; Zhang, Bing; Sun, Kun; Lu, Yanan (Frontiers in Genetics, 2023)
Atrioventricular septal defect (AVSD) is a deleterious subtype of congenital heart diseases (CHD) characterized by atrioventricular canal defect. The pathogenic genetic changes of AVSD remain elusive, particularly for copy number variation (CNV), a large segment variation of the genome, which is one of the major forms of genetic variants resulting in congenital heart diseases. In the present study, we recruited 150 AVSD cases and 100 healthy subjects as controls for whole exome sequencing (WES). We identified total 4255 rare CNVs using exon Hidden Markov model (XHMM) and screened rare CNVs by eliminating common CNVs based on controls and Database of Genomic Variants (DGV). Each patient contained at least 9 CNVs, and the CNV burden was prominently presented in chromosomes 19,22,21&16. Small CNVs (<500 kb) were frequently observed. By leveraging gene-based burden test, we further identified 20 candidate AVSD-risk genes. Among them, DYRK1A, OBSCN and TTN were presented in the core disease network of CHD and highly and dynamically expressed in the heart during the development, which indicated they possessed the high potency to be AVSD-susceptible genes. These findings not only provided a roadmap for finally unveiling the genetic cause of AVSD, but also provided more resources and proofs for clinical genetics.